2018
DOI: 10.1126/science.aat9393
|View full text |Cite
|
Sign up to set email alerts
|

East Asian hydroclimate modulated by the position of the westerlies during Termination I

Abstract: Speleothem oxygen isotope records have revolutionized our understanding of the paleo East Asian monsoon, yet there is fundamental disagreement on what they represent in terms of the hydroclimate changes. We report a multiproxy speleothem record of monsoon evolution during the last deglaciation from the middle Yangtze region, which indicates a wetter central eastern China during North Atlantic cooling episodes, despite the oxygen isotopic record suggesting a weaker monsoon. We show that this apparent contradict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
155
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(168 citation statements)
references
References 75 publications
12
155
1
Order By: Relevance
“…While our results are based on the numerical experiments, comparing speleothem δ 18 O with other proxy data can provide additional clues to interpret speleothem δ 18 O. For example, Zhang et al () compared a speleothem δ 18 O record with a speleothem trace metal record, which is believed to represent local precipitation and revealed the decoupling of precipitation and speleothem δ 18 O signals. Also, a recent finding of marine sediments in the East China Sea (Clemens et al, , Site U1429 of the International Ocean Discovery Program) representing the monsoon runoff showed that it did not feature the 23‐kyr cycles present in speleothem records.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…While our results are based on the numerical experiments, comparing speleothem δ 18 O with other proxy data can provide additional clues to interpret speleothem δ 18 O. For example, Zhang et al () compared a speleothem δ 18 O record with a speleothem trace metal record, which is believed to represent local precipitation and revealed the decoupling of precipitation and speleothem δ 18 O signals. Also, a recent finding of marine sediments in the East China Sea (Clemens et al, , Site U1429 of the International Ocean Discovery Program) representing the monsoon runoff showed that it did not feature the 23‐kyr cycles present in speleothem records.…”
Section: Discussionmentioning
confidence: 87%
“…This pattern is similar to the leading mode of interannual precipitation variability in East Asia (Day et al, ). Speleothem trace element ratios also suggest that low values of speleothem δ 18 O in central China can coincide with dryness instead of wetness in that region (Zhang et al, ). This, however, is not enough to reach a conclusion regarding central China receiving less precipitation in P min , since similar simulations with other models like EC‐Earth and GFDL‐CM2.1 do not clearly show less precipitation in central China (Bosmans et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Hopanoid mass accumulation rates (blue) (Xie et al, ) and mean annual precipitation reconstructed by the pollen‐transfer function method (blue) (Xiao et al, ) from Dajiuhu peatland. (f) Stalagmite ARM/SIRM record from Heshang cave (blue) (Xie et al, ), and the leading principal component (PC1) of six trace element ratio time series (Sr/Ca, Ba/Ca, and Mg/Ca) from Haozhu cave (red) (Zhang et al, ). (g) Paleoprecipitation record based pollen assemblages from Gonghai lake (blue) (Chen et al, ) and magnetic susceptibility record from Lantian loess section (red) (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Speleothem δ 18 O records in southern and central China have been regarded as yielding the most significant and reliable information about EASM changes on various timescales (Cheng et al, ; Wang et al, ). However, the climatic interpretation of speleothem δ 18 O remains highly controversial in terms of large‐scale shifts in Asian summer circulation, and more “local‐scale” changes in precipitation (Caley et al, ; Maher & Thompson, ; Zhang et al, ). The traditional paradigm links the cave δ 18 O signals as a proxy for regional rainfall of the EASM, with higher EASM rainfall corresponding to more depleted δ 18 O (Cheng et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%